Utilization of mung bean sprout waste Vigna radiata hydrolyzed cellulase enzyme in feed on the digestibility of Nile tilapia Oreochromis sp. - Grenda Audia Wuryas Pradita Negara; Mia Setiawati; Julie Ekasari; Dedi Jusadi (Jurnal Akuakultur Indonesia, 2026)
This study evaluated the utilization of mung bean sprout waste flour hydrolyzed by cellulase enzyme (LTe) as the feed ingredient of red Nile tilapia weighing 10.00 ± 0.01 g/seed and 7.00 ± 0.15 in length. This study used two stages, each consisting of four treatments and four replications. The first step was performed by evaluating LTe flour added with cellulase enzyme of 0 g/kg (control), 0.4 g/kg, 0.8 g/kg, and 1.2 g/kg. The second step was the digestibility test of LTe and growth performance on red Nile tilapia seeds. The results showed that the addition of cellulase enzyme at a 1.2 g/kg was significantly able to reduce the crude fiber of LTe with 78.19% %, hemicellulose at 19.22%, neutral detergent fiber at 41.69%, acid detergent fiber at 61.85%, lignin 64.06%, cellulose 62.47% besides having the best value of ingredient, protein, and energy digestibility. The test results on the growth performance of red Nile tilapia seeds fed with LTe feed with a dose of 1.2 g/kg cellulase enzyme have the highest value significantly different from the control feed based on the value of daily growth rate (SGR), ratio efficiency protein (REP), protein retention (PR), and improvement of feed conversion ratio (RKP).   Keywords: cellulase enzyme, digestibility, growth performance, mung bean sprout waste, tilapia   Abstrak Penelitian ini mengevaluasi pemanfaatan tepung limbah kecambah kacang hijau yang dihidrolisis enzim selulase (LTe) sebagai bahan baku pakan pada benih ikan nila merah dengan bobot 10,00 ± 0,01 g/ekor dan panjang 7,00 ± 0,15 cm. Penelitian ini menggunakan dua tahap dan masing-masing tahap terdiri dari empat perlakuan dan empat ulangan. Tahap pertama dilakukan evaluasi tepung LTe sebesar 0 g/kg (kontrol), 0,4 g/kg, 0,8 g/kg, dan 1,2 g/kg. Tahap kedua dilakukan uji kecernaan bahan LTe dan kinerja pertumbuhan benih ikan nila merah. Hasil penelitian menunjukkan bahwa penambahan enzim selulase pada dosis 1,2 g/kg signifikan mampu menurunkan serat kasar LTe sebesar 78,19 %, hemiselulosa 19,22%, neutral detergent fiber 41,69%, acid detergent fiber 61,85%, lignin 64,06%, selulosa 62,47% dan memberikan nilai tertinggi terhadap kecernaan bahan, kecernaan protein, dan kecernaan energi. Hasil uji terhadap kinerja pertumbuhan benih ikan nila merah yang diberi pakan LTe dengan enzim selulase dosis 1,2 g/kg memiliki nilai tertinggi berbeda nyata terhadap pakan kontrol berdasarkan nilai laju pertumbuhan harian (SGR), retensi protein (PR), rasio efisiensi protein (REP) dan perbaikan nilai rasio konversi pakan (RKP). Kata kunci: enzim selulase, ikan nila merah, kecernaan, kinerja pertumbuhan, limbah kecambah kacang hijau